(untitled) (Research, Society and Development, 2020)
Among the problems related to water resources in Brazil, besides the unconscious and excessive use made by the population, it is their irregular geographical distribution. One of the most important rivers and which constitutes the largest hydrographic basin in Pernambuco is the Pajeú. As it is an intermittent river, one of the main initiatives of the government to increase the water supply over time was and continues to be the construction of large hydraulic works such as weirs and dams, whose purpose is to store water for supplying cities, cultivation of land and animal breeding. However, when viewing the structures of these reservoirs and their respective storage basins along the basin, it appears that the current aspect of the operational conditions of these water bodies presents a visible and worrying decay, largely due to the absence of power actions aimed at their management and conservation. Due to this situation of water structure degradation, the present work proposed to raise the level of deterioration in which the 6 of the main water bodies of the Pajeú River and its tributaries are found. It was found that most structures present a worrying abandonment situation and can be classified as having high associated potential damage and high risk category, therefore, prone to ruptures if they remain without the short-term contemplation of a preventive maintenance plan.